KISS-1 knockdown inhibits cell growth, migration, and invasion in HTR-8/SVneo cells by regulating the GRP54-mediated PI3K/AKT signaling pathway - Lingna Chen; Yuying Ruan; Liping Ni; Guiting Wang; Yajuan Gao; Jindi Zhang; Dingheng Li; Haiou Xu (Autoimmunity, 2024)
Recurrent spontaneous abortions (RSA) affect reproductive health and increase the risk of subsequent abortions. To investigate the role of KISS-1/GPR-54 signaling in RSA progression. Villus tissue was collected from RSA patients, and human trophoblastic HTR-8/SVneo cells were used. KISS-1 and GRP54 levels were detected using RT-qPCR and immunohistochemistry. Western blotting was performed to analyze ZO-1 and ZEB1 levels. Cell proliferation was determined via CCK-8 and cell clone formation assays. Transwell assays were performed to assess cell migration and invasion abilities. KISS-1 was down-regulated in the villus tissues of RSA patients. KISS-1 overexpression dramatically inhibited trophoblast proliferation, migration, and invasion. Mechanistically, ZEB1 expression was down-regulated, whereas ZO-1 expression was up-regulated, after KISS-1 overexpression. GPR54 silencing neutralized the effect of KISS-1 in HTR-8/SVneo cells. Additionally, KISS-1 overexpression inactivated the PI3K/AKT signaling pathway through GRP54. The KISS-1/GPR-54 signaling axis regulates RSA progression by regulating the PI3K/AKT signaling pathway.